Kindbettgeschenke Untersuchungen zu Ursprung, Form und Funktion von kunstgewerblichen Objekten als Gaben an die Mutter nach der Geburt - Brüderle, Nicole (Universitätsverlag Göttingen, 2016)
The term childbed presents is understood to mean gifts that were presented to the mothers of new-born babies in childbed. Presents for the new mother given for example during visits by relatives, friends and neighbours, initially consisted of food and drink. Later they could also include applied art objects. The custom of presenting childbed presents has a long tradition and still partially continues until today. In the present study, applied art objects which can be identified as childbed presents are analyzed and discussed in relation to their art historical development from the early modern period to the early 19th century. In regard to their cultural and historical context, questions about the form, content and function of these gifts will be investigated. In doing so a special field of early modern art and culture becomes accessible for the first time.